2019
DOI: 10.3233/jifs-179109
|View full text |Cite
|
Sign up to set email alerts
|

Big data analysis techniques for intelligent systems

Abstract: Recently, Internet of Things (IoT), Cloud, Big Data and AI gained a great attention as the most research topics. They cover not only information and communication technology, but also all kinds of intelligent systems in our society, including business, finance, industry, manufacture, management, and environment. As a result of the extensive use of these new technologies, a huge volume of data in different formats are generated much faster than before. Big data, characterized by high volume, variety and velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In the probabilistic model of text representation, it is assumed that there is a sufficiently large ideal text corpus document set and a string used by the user for query so that the query processing can be regarded as processing the attributes of the ideal result document set. Some attributes of the documents cannot be obtained exactly, because some feature attributes are fuzzy and invisible at the time of retrieval and contribute differently to the importance of the task [ 12 ]. Therefore, the probability values of these attributes need to be estimated at the early stage of the query to determine the importance of the processing task.…”
Section: Analytical Design Of English Writing Neural Network Algorithmmentioning
confidence: 99%
“…In the probabilistic model of text representation, it is assumed that there is a sufficiently large ideal text corpus document set and a string used by the user for query so that the query processing can be regarded as processing the attributes of the ideal result document set. Some attributes of the documents cannot be obtained exactly, because some feature attributes are fuzzy and invisible at the time of retrieval and contribute differently to the importance of the task [ 12 ]. Therefore, the probability values of these attributes need to be estimated at the early stage of the query to determine the importance of the processing task.…”
Section: Analytical Design Of English Writing Neural Network Algorithmmentioning
confidence: 99%
“…Some researchers start from the basis of learning theory and verify through experiments that learners' learning effect is significantly improved with the assistance of new technology, which lays a solid foundation for further research and application of mobile APP learning [8]. Farouk A et al conducted experiments on discrete data modeling and simulation of intelligent interactive English teaching, and the experiments focused on whether the service is effective when applied to educational teaching and learning [9]. Bryndin E et al conducted a study on smart interactive English teaching discrete data modeling and simulation, and the results indicated that discrete data modeling is perfectly feasible as a mobile APP learning aid for educational teaching.…”
Section: Related Workmentioning
confidence: 99%
“…Ghorbani and Ghousi conducted an in-depth study on educational management and data mining techniques in colleges and universities, using data mining related algorithms, and integrated a simple voting strategy through the study of simple improvement method of Apriori algorithm and ID3 algorithm, which has improved the educational management of students in colleges and universities and provided valuable guidance for students' training [ 10 ]. Farouk and Zhen used the educational technology of OLAM to analyze the education and admission of colleges and universities and identified the reasons and potentially useful information affecting students' enrolment through data mining techniques based on the educational data of previous years [ 11 ].…”
Section: Related Workmentioning
confidence: 99%
“…Through the above literature, we can see that data mining is more oriented to the improvement of algorithms of data mining technology and the mining of existing education management data to analyze the intrinsic relationship between their different attribute values, but there is relatively little research on the valuable information that affects the relationship between new students' arrival rate and education management decisions. The purpose of this paper is to analyze and study educational management data from this perspective using mining techniques [ 11 , 18 ]. The development of an educational management information management system plays an important role in promoting the development of higher education informatization.…”
Section: Related Workmentioning
confidence: 99%